Measuring the Dynamic Stock Buffer Management Approach Fit to the Customer Needs Based on the (Balanced) Critical Factor Index Method - Kaakinen, Sanna-Mari (My University, 2012)
In this research, the fit between the Dynamic Stock Buffer Management (DSBM) approach, designed for inventory control and optimization, and the customers’ needs under the current circumstances is studied. The customer is the purchasing department in ABB Oy, Distribution Automation Business unit in Vaasa, Finland. The purchasing function of another business unit, Low Voltage Products, is treated as a reference in the research. The research goals encompass identifying both the critical factors and the DSBM factors, and the culmination of the research is to analyze and examine the reciprocal fit between these factors. The main goal is to analyze the suitability of the DSBM approach to the Distribution Automation purchasing function based on the fit between the critical factors and DSBM factors. The research method used in this research is the (Balanced) Critical Factor Index method. It is chosen because of its applicability and flexibility and the wide practical and theoretical basis it lies on. In this research the method has been further developed to fit the research question and composition. The research data is gathered from a triangular basis: the Distribution Automation purchasers, the Low Voltage Products purchasers and an external consultant. The core theoretical contribution deals with the applications of the research method; the research proved the method applicability to a new kind of research. The practical contribution lies in identification of the critical factors in both Distribution Automation and Low Voltage Products purchasing functions; the critical factor identification is derived to sensing customer needs. Also identification of the Dynamic Stock Buffer Management factors and comprehensive understanding of the approach enable the evaluation of the fit to the customer needs. KEYWORDS: Balanced Critical Factor Index, Critical factor index, Customer Needs, Dynamic Stock Buffer Management.
Keywords: fi=Tuotantotalous|en=Industrial Management|